SUSTAINABLE DEVELOPMENT GOALS (SDGS) TOWARD INDEPENDENT VILLAGES IN THE STRATEGIC BORDER AREA - Nasution, Mimin Sundari; Afrizal, Afrizal (International Conference On Social Science Education, 2023)
State border areas are areas that have strategic positions. Because of this weakness becomes a strategic issue in the border area as the front porch of the country. The border area of Indonesia as the external face of the country is impressed if its management is more predicated on a safety approach (safety belt approach). Villages in Indonesia are still areas that are quite difficult to untangle; it is often narrated that he is lagging in development affairs so that social, economic, infrastructure and other developments seem to be neglected. The Village Sustainable Development Goals are a development concept that places more emphasis on environmentally friendly development and protects the culture and interests of the local community. This study aims to see how the goals of sustainable development (SDGs) are in the border villages of the Rokan Hilir district. This study uses a qualitative approach. Data collection was carried out through in-depth interviews, observation, and interactive photography techniques to gain an in-depth understanding of the research problem. Informants were determined by purposive sampling technique. After the data has been collected, it is analyzed using an analytical approach using the N-Vivo 12 to explain, present and place the data so that conclusions can be drawn and drawn. To achieve sustainability, cooperation is needed in the 3 dimensions of the SDGs which balances development on the economic, social, and environmental dimensions. The results of the study show that the Village Sustainable Development Goals, especially Teluk Pulai Village in the border area of Rokan Hilir District, have not been realized based on indicators of fulfilling sustainability. Apart from that, it can also be seen from the SDGs achievement targets that were not achieved which ultimately had an impact on the Village SDGs Score of 35.96 and the Developing Village Index (IDM) with a Developing status. The SDGs goals in the border area have not been realized, including a lack of village development programs where the planned programs only focus on meeting the needs of the village community so the SDGs Village goals needed by the community are not planned.